Environmental drivers of the benthic macroinvertebrates community in a hypersaline estuary (Northeastern Brazil) - Carlinda Railly Ferreira Medeiros (Acta Limnologica Brasiliensia)
Abstract Introduction The estuarine community of benthic macroinvertebrates spatially varies in response to changes in environmental variables in these ecosystems. Understanding this variability helps our understanding the mechanisms structuring these communities. Aim Assess the structural aspects of the benthic macroinvertebrate community in a hypersaline estuary, and to relate to environmental variables that influence the community structure along the estuary. Methods The study was conducted at Tubarão river estuary in May 2015. We sampled two estuarine areas (upper and lower), and in each zone were sampled six points composed of two replicas, one sampled in sandy bottom and the other in muddy bottom. Samples of benthic macroinvertebrates and estuarine environmental variables were collected. Environmental drivers of the benthic macroinvertebrate community were determined by Distance-based Linear Models analysis. The contribution of individual species to the dissimilarity between the areas and substrate types were determined by analysis of the percentage of similarity. Results The composition of benthic macroinvertebrate community differed between the upper and lower areas, although it was similar between the muddy and sandy bottoms. The variation in the benthic community between areas was mainly related to the influence of salinity in the upper area. In the lower area, the variation of the macroinvertebrates was related to salinity, associated with other variables in the sandy (temperature, turbidity and dissolved oxygen) and muddy (temperature, total dissolved solids and dissolved oxygen) substrates. Taxa which contributed most to the dissimilarity between the upper and lower areas were Nereididae (17.89%), Anomalocardia brasiliana (15%) and Cirratulidae (10.43%). Conclusions Salinity was the main driver of the structural aspects of the benthic macroinvertebrate community in the upper area of the estuary, although in the lower area a set of variables have structured benthic macroinvertebrates in the hypersaline estuary studied. In addition, the largest mangrove cover and less influence of the tide, may have favored the greater abundance of macroinvertebrates in the upper area.